A Case of Acute ST elevated Myocardial Infarction Managed with Primary PCI: Launched Case of University Cardiac Center - Ahsan, Sayed Ali; Hasan, Md Nazmul; Siddique, Md Abu; Banerjee, Sajal Krishna; Salim, Md Abu (University Heart Journal, 2014)
Coronary reperfusion with primary percutaneous coronary intervention (PPCI) or fibrinolytic therapy improves outcomes in patients with acute ST elevation myocardial infarction (STEMI) or an MI with a new or presumably new left bundle branch block or a true posterior MI. If performed in a timely fashion, PPCI is the reperfusion therapy of choice compared to fibrinolysis because it achieves a higher rate of TIMI 3 flow. Here we describe a case of acute ST elevated inferior myocardial infarction managed with primary percutaneous coronary intervention as a launching case in the University Cardiac Center ofBangabandhu Sheikh Mujib Medical University. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19518 University Heart Journal Vol. 9, No. 1, January 2013; 67-69